Eurostat yearbook 2003 : the statistical guide to Europe: data 1991-2001. (Panorama of the European Union, 2003)
For the first time, the Eurostat yearbook is published as a combined paper and CD-ROM publication. The CD-ROM version allows you to extract data and to create your own tables. The references for further reading are linked electronically to the Internet presentation of the respective publication, or, if the publication can be downloaded free of charge, to the publication itself. More Hyperlinks to the Eurostat Internet site or to web sites of other General Directorates of the European Commission are available.The logo for the Structural Indicators (the statistical basis of the European Commission's annual Spring Report) is linked to Eurostat's Internet pages presenting these indicators.A new chapter, 'The European Union in the global context', provides a wider perspective of the EU's position in the world.A special 'In the spotlight' section outlines the situation in the EU candidate countries.